Comparison of the Effectiveness of Series and Parallel Monopolar Electrode Arrangements in Electrocoagulation Reactors for Reducing Color and COD - Naurah Thifal Safitri; Mohamad Mirwan; Restu Hikmah Ayu Murti (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Industrial batik wastewater contains dyes and organic compounds at high concentrations,posing a potential threat to aquatic environments. This study aims to evaluate theeffectiveness of electrocoagulation using series and parallel monopolar electrodeconfigurations in reducing the levels of methylene blue, methyl red, and chemical oxygendemand (COD) in batik wastewater. The process was carried out in batches, withvariations in electrode configuration, voltages of 6 and 9 volts, and contact times of 30–90 minutes, using aluminium and iron electrodes. Color concentration analysis wasperformed using UV–Vis spectrophotometry, while COD was analyzed using the closedreflux method. The results showed that increasing the voltage and contact time improvedthe removal efficiency of all parameters. The parallel monopolar configuration providedthe best performance, with reduction efficiencies of 95.23% for methylene blue, 90.02%for methyl red, and 71.21% for COD. This was influenced by a more even currentdistribution and more effective coagulant formation. Parallel monopolarelectrocoagulation has the potential to be applied as an alternative method for treatingbatik wastewater.Contribution to Sustainable Development Goals (SDGs):SDG 3: Good Health and Well-BeingSDG 6: Clean Water and SanitationSDG 11: Sustainable Cities and CommunitiesSDG 14: Life Below Water